The Alexandreis of Walter of Châtillon : a twelfth-century epic : a verse translation - Walter, of Châtillon, active 1170-1180 (Middle Ages series., 1996)
David Townsend's translation - the first ever into English verse - affords modern readers a vivid sense of the aesthetic appeal and sophisticated artistry of Walter's poem. A concise introduction sets out the poem's background and significance in literary history, while also suggesting how Walter's text resonates with the literary sensibilities of our own times.